2019
DOI: 10.1021/acsbiomaterials.8b01541
|View full text |Cite
|
Sign up to set email alerts
|

Regeneration of Paralyzed Vocal Fold by the Injection of Plasmid DNA Complex-Loaded Hydrogel Bulking Agent

Abstract: Various growth factor delivery systems were used in the treatment of glottal insufficiency; however, relatively little attention has been paid to a gene delivery system for aspects of active vocal fold (VF) regeneration. Herein, we present a plasmid DNA (pDNA; bFGF gene encoding) complex-loaded alginate (ALG)/hyaluronic acid (HA) mixture hydrogel dispersed with polycaprolactone (PCL) microspheres that can enhance simultaneous regeneration of VF muscle and lamina propria, as well as have a bulking effect on atr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 66 publications
0
6
0
Order By: Relevance
“…Chronic inflammatory diseases not only have a persistent pro-inflammatory response but also have the possibility of an uncontrolled inflammatory response [ 18 20 ]. It has been found that almost all kidney diseases are accompanied by secretion of inflammatory factors and infiltration of immune cells, while macrophages have strong plasticity in acute and chronic inflammation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chronic inflammatory diseases not only have a persistent pro-inflammatory response but also have the possibility of an uncontrolled inflammatory response [ 18 20 ]. It has been found that almost all kidney diseases are accompanied by secretion of inflammatory factors and infiltration of immune cells, while macrophages have strong plasticity in acute and chronic inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been shown that with the decline of renal function in patients with CKD, the body will continue to show low levels of inflammation in the absence of systemic or local obvious clinical manifestations of infection, mainly with the persistent increase of tumor necrosis factor (TNF-α), interleukin-6 (IL-6) and monocyte chemoattractant protein-1 (MCP-1) as the signal [17]. Chronic inflammatory diseases not only have a persistent pro-inflammatory response but also have the possibility of an uncontrolled inflammatory response [18][19][20]. It has been found that almost all kidney diseases are accompanied by secretion of inflammatory factors and infiltration of immune cells, while macrophages have strong plasticity in acute and chronic inflammation.…”
Section: Plos Onementioning
confidence: 99%
“…When injected into the vocal fold of rabbits with laryngeal nerve denervation, an unprecedented recovery of vocal function was achieved. 62 …”
Section: Controlled Delivery Of Therapeutic Biomolecules From Polysac...mentioning
confidence: 99%
“…Regeneration of laryngeal tissues and restoration of intrinsic laryngeal functions are challenging problems that have yet to be addressed by existing injectable materials. Previously, with experience of injection laryngoplasty of diverse materials, including polycaprolactone, Pluronic F127, poly (lactic-co-glycolic acid) (PLGA), and adipose-derived extracellular matrix (ECM) [ 13 18 ], we have accumulated various experimental and analytical methods to assess the properties of injectable materials.…”
Section: Introductionmentioning
confidence: 99%